Use of Container Materials as an Enhancement Effort to identify the letters of hijayah for Early Age Children - Agus Sriyanto; Farihah, Elyaum (PAUD Lectura: Jurnal Pendidikan Anak Usia Dini, 2023)
The purpose of the study was to find out how to improve recognizing hijaiyah letters in early childhood, inhibiting and supporting factors by using used materials. Field research in Kindergarten Dharma Wanita Kauman I with the form of this research is a descriptive qualitative case study. The method used to collect research data is through interviews, observation and documentation. The methods for analyzing research data are data reduction, data presentation (display), and drawing conclusions or verification. The results of the study were: (1) after the act of learning through the media of used materials increased by 90% (22 of 25 students) they were able to recognize hijaiyah letters well, (2) the presence of used material media could also attract children's interest in learning because it has a variety of -various shapes and colors, (3) inhibiting factors: lack of parental attention, parents only rely on children's learning at school. Supporting factors: the enthusiasm of children in introducing hijaiyah letters using various APEs, used media media make children more enthusiastic and not easily bored.